TRPA1 and TRPV1 Antagonists Do Not Inhibit Human Acidosis-Induced Pain - Schwarz, Matthias G.; Namer, Barbara; Reeh, Peter; Fischer, Michael (Journal of Pain, 2017)
Acidosis occurs in a variety of pathophysiological and painful conditions where it is thought to excite or contribute to excitation of nociceptive neurons. Despite potential clinical relevance the principal receptor for sensing acidosis is unclear, but several receptors have been proposed. We investigated the contribution of the acid-sensing ion channels, transient receptor potential vanilloid type 1 (TRPV1) and transient receptor potential ankyrin type 1 (TRPA1) to peripheral pain signaling. We first established a human pain model using intraepidermal injection of the TRPA1 agonist carvacrol. This resulted in concentration-dependent pain sensations, which were reduced by experimental TRPA1 antagonist A-967079. Capsaicin-induced pain was reduced by the TRPV1 inhibitor BCTC. Amiloride was used to block acid-sensing ion channels. Testing these antagonists in a double-blind and randomized experiment, we probed the contribution of the respective channels to experimental acidosis-induced pain in 15 healthy human subjects. A continuous intraepidermal injection of pH 4.3 was used to counter the buffering capacity of tissue and generate a prolonged painful stimulation. In this model, addition of A-967079, BCTC or amiloride did not reduce the reported pain. In conclusion, target-validated antagonists, applied locally in human skin, have excluded the main hypothesized targets and the mechanism of the human acidosis-induced pain remains unclear. PERSPECTIVE: An acidic milieu is a trigger of pain in many clinical conditions. The aim of this study was to identify the contribution of the currently hypothesized sensors of acid-induced pain in humans. Surprisingly, inhibition of these receptors did not alter acidosis-induced pain.
EVALuna2:33346